2022
DOI: 10.1021/acs.chemmater.2c01154
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Large-Area Polycrystalline Transition Metal Dichalcogenides from 100 °C through Control of Plasma Chemistry

Abstract: Two-dimensional transition metal dichalcogenides, such as MoS 2 , are intensely studied for applications in electronics. However, the difficulty of depositing large-area films of sufficient quality under application-relevant conditions remains a major challenge. Herein, we demonstrate deposition of polycrystalline, wafer-scale MoS 2 , TiS 2 , and WS 2 films of controlled thickness at record-low temperatures down to 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(59 citation statements)
references
References 83 publications
(172 reference statements)
3
56
0
Order By: Relevance
“…An example of this from our earlier work is shown Figure 1c, illustrating how increasing H 2 flow ratio (eq 1) from 0.20 to 0.80 at 150 °C changes the resulting film from amorphous MoS 3.5 to crystalline MoS 2 . 39 However, the increase in the H 2 flow ratio also leads to incorporation of H dopants into the films, resulting in high carrier densities, a drawback for many semiconductor applications. In addition, high H 2 flow ratios, which we denote as a subscript of B (e.g., B 0.80 ) lead to rough morphology (Figure 1c).…”
Section: Concept Of Developed Peald Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of this from our earlier work is shown Figure 1c, illustrating how increasing H 2 flow ratio (eq 1) from 0.20 to 0.80 at 150 °C changes the resulting film from amorphous MoS 3.5 to crystalline MoS 2 . 39 However, the increase in the H 2 flow ratio also leads to incorporation of H dopants into the films, resulting in high carrier densities, a drawback for many semiconductor applications. In addition, high H 2 flow ratios, which we denote as a subscript of B (e.g., B 0.80 ) lead to rough morphology (Figure 1c).…”
Section: Concept Of Developed Peald Processesmentioning
confidence: 99%
“…38 Recently, we showed that tailoring the plasma deposition chemistry enables a decrease of deposition temperature of both semiconducting and metallic TMDCs to record low 100 °C. 39 The deposition of stoichiometric and crystalline MoS 2 , TiS 2 , and WS 2 films was achieved by addition of sufficient hydrogen to the H 2 S plasma feed gas, which prevents excess S incorporation from otherwise happening at these low temperatures. However, tailoring the chemistry of a single plasma step in such a manner offers limited control over film properties, as the plasma species play multiple simultaneous roles including removal of ligands of the metal precursor, deposition of sulfur, and supplying energy in the form of low-energy ions and other reactive species for creation and healing of defects.…”
Section: Introductionmentioning
confidence: 99%
“…The current levels are admittedly not optimized; as stated before, the aim of this transistor study was not to focus on a device figure of merit but rather to extract insight into the quality and current carrying capability of the material thin films. However, the current levels are comparable with FETs fabricated using ALD thin films processed only at low temperatures, namely, 100–300 °C . Performing a high-temperature annealing or synthesis can undoubtedly and impressively improve the current levels and FET device figures of merit , through better crystallinity and reduced defect concentrations, but that would limit the use to front-end-of-line applications or relying on risky layer transfer.…”
Section: Resultsmentioning
confidence: 97%
“…Our “35 Voices” initiative will also begin so that we may hear what motivates materials researchers from all over the world. To kick off our 35th year, however, we start by highlighting 35 of the most cited and downloaded manuscripts published in 2022. …”
mentioning
confidence: 99%
“…MXenes and layered dichalcogenides (Table ) as well as covalent organic framework (COF) materials (Table ) were also well-represented. The contributions on MXenes include a Methods/Protocols paper that provides practical insights for the synthesis and processing of these exciting materials .…”
mentioning
confidence: 99%